HUBUNGAN KELENTUKAN PERGELANGAN TANGAN DAN POWER OTOT LENGAN-BAHU DENGAN HASIL AKURASI SMASH BULUTANGKIS PB FORTUNA PASIR PENGARAIAN - Krismon Krismon; Ni Putu Nita Wijayanti; Syahriadi Syahriadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Based on the problem, it was determined that their smashing ability was not good, the direction of the rooster was flat and did not dive, the shot was returned easily, the ball was not tight, the rooster often went out of the field or did not aim for the target sometimes there was still something stuck in the net this would be due to wrist flexibility and arm-shoulder muscle strength. The aim of this research was to determine wrist flexibility and arm-shoulder muscle strength with great accuracy results. The population in this research were all athletes of PB badminton Fortuna Pasir Pengaraian, a total of 8 subjects. This research uses a total sampling technique. The instruments in this research are test goniometer, two-handed exercise ball, and smash accuracy. Based on the analysis of the normality test, X1 data produces LoMax of 0.282 and Ltable of 0.285 and X2 data produces LoMaks of 0.276 and Ltable of 0.285, while the Y variable produces LoMax of 0.283 and Ltable of 0.285. This means that LoMax < Ltable , then the data is normally distributed. Thus, based on the hypothesis test using the product moment test on variables X1, X2 on variable Y, namely data 0.993 > 0.754 Rcount > Rtable, there is a significant relationship between wrist flexibility and shoulder arm muscle strength with smash accuracy results for PB Fortuna Pasir Pengaraïan.Key Words: Wrist Flexibility, Arm-Shoulder Muscle Strength, Smash Accuracy